Use of offspring mesenchymal stem cells to study in-utero maternal-fetal programming - Chaves, Alec B. (East Carolina University, 2021)
Offspring born from mothers with obesity are at a greater risk for obesity, cardiovascular disease, and diabetes, forming a vicious cycle across generations. Although metabolic diseases are often thought to result from lifestyle habits, the classic epidemiological studies of the late David Barker showing low birth weight is associated with mortality from cardiovascular disease in adulthood has added insight into the current dogma underlying the pathogenesis of metabolic diseases. This theory, now coined the Developmental Origins of Health and Disease hypothesis, postulates that an unfavorable intrauterine environment will program an adverse metabolic phenotype, thus increasing the risk of developing diseases postnatally. Therefore, pregnancy is a critical window of fetal development that may shape the future trajectory of offspring metabolic health. However, lifestyle inventions during pregnancy, such as exercise, have been shown to improve offspring's metabolic health. Thus far, most of these studies have been limited to the use of rodents and non-human primates. To translate these findings to the human condition, our lab has successfully collected mesenchymal stem cells (MSCs) from human offspring from two clinical trials: Healthy Start Study (R01DK076648, ClinicalTrials.gov identifier NCT02273297) and ENHANCED (ClinicalTrials.gov Identifier: NCT03517293) to investigate the relationship between maternal obesity, metabolism, and exercise on offspring mesenchymal stem cells metabolism, respectively. In aim one of this dissertation, we isolated mesenchymal stem cells (MSCs) from the umbilical cord tissue of infants born to mothers of normal weight (NW) or mothers with obesity (Ob). Insulin stimulated glycogen storage was determined in MSCs undergoing myogenesis in vitro. There was no difference in insulin action when stratified by maternal BMI. However, maternal free fatty acid concentration, cord leptin, and intracellular triglyceride content were positively correlated with insulin action. Furthermore, MSCs from offspring born to mothers with elevated FFA displayed elevated activation of the mTOR signaling pathway. Taken together, infants born to mothers with elevated lipid availability have greater insulin action in MSC; this finding may be an indicator of a "growth or storage phenotype" which may increase nutrient storage capacity during periods of maternal overnutrition. In aim two of the dissertation, expecting mothers, were randomized into one of two groups: aerobic exercise (AE) or non-exercise control (CON). The AE group completed 150 min of weekly moderate-intensity exercise during pregnancy (16 to 36+ weeks) while controls attended stretching sessions. Following delivery, MSCs were isolated from the umbilical cord of the offspring and experiments were done in the undifferentiated (D0) or myogenically differentiating (D21) state. Radiolabeled glucose and fatty acid tracers were used to measure glucose and lipid metabolism, respectively. AE-MSCs have increased insulin action, reduced non-oxidized glucose metabolite (NOGM) production, and trending increases in glucose partitioning towards oxidation at D0. At D21, AE-MSCs had trending elevations and reductions in glucose oxidation and NOGM production, respectively, resulting in significant elevations in glucose partitioning towards oxidation. Furthermore, immunoblot analysis revealed a significant increase in complex I expression in the AE-MSCs at D21. Basal and palmitate-stimulated lipid metabolism was similar between groups at D0 and D21. Together, these data provide the first evidence of a programmed metabolic phenotype in human offspring cells specific to the substrate glucose, resulting from maternal aerobic exercise.
Keywords: prenatal; Maternal-fetal exchange; Obesity in women--Health and hygiene; Obesity--Prevention; Exercise for pregnant women; Mesenchymal stem cells; Fetus--Physiology